Cross-Species BAC Mapping Highlights Conservation of Chromosome Synteny across Dragon Lizards (Squamata: Agamidae) - Alam, Shayer Mahmood Ibney; Altmanová, Marie; Prasongmaneerut, Tulyawat; Georges, Arthur; Sarre, Stephen D; Nielsen, Stuart V; Gamble, Tony; Srikulnath, Kornsorn; Rovatsos, Michail; Kratochvíl, Lukáš; Ezaz, Tariq (Genes, 2020)
Dragon lizards (Squamata: Agamidae) comprise about 520 species in six subfamilies distributed across Asia, Australasia and Africa. Only five species are known to have sex chromosomes. All of them possess ZZ/ZW sex chromosomes, which are microchromosomes in four species from the subfamily Amphibolurinae, but much larger in Phrynocephalus vlangalii from the subfamily Agaminae. In most previous studies of these sex chromosomes, the focus has been on Australian species from the subfamily Amphibolurinae, but only the sex chromosomes of the Australian central bearded dragon (Pogona vitticeps) are well-characterized cytogenetically. To determine the level of synteny of the sex chromosomes of P. vitticeps across agamid subfamilies, we performed cross-species two-colour FISH using two bacterial artificial chromosome (BAC) clones from the pseudo-autosomal regions of P. vitticeps. We mapped these two BACs across representative species from all six subfamilies as well as two species of chameleons, the sister group to agamids. We found that one of these BAC sequences is conserved in macrochromosomes and the other in microchromosomes across the agamid lineages. However, within the Amphibolurinae, there is evidence of multiple chromosomal rearrangements with one of the BACs mapping to the second-largest chromosome pair and to the microchromosomes in multiple species including the sex chromosomes of P. vitticeps. Intriguingly, no hybridization signal was observed in chameleons for either of these BACs, suggesting a likely agamid origin of these sequences. Our study shows lineage-specific evolution of sequences/syntenic blocks and successive rearrangements and reveals a complex history of sequences leading to their association with important biological processes such as the evolution of sex chromosomes and sex determination.
Keywords: hadi; Cytogenetics; Chromosomes, Artificial, Bacterial; analýza určování pohlaví; Sex Chromosomes; umělé bakteriální chromozomy; pohlavní chromozomy; BACs; karyotypizace; Sex Determination Processes; Karyotyping; molekulární evoluce; Evolution, Molecular; Lizards; cytogenetika; Synteny; ještěři; FISH; synteny; sex chromosomes; Animals; ženské pohlaví; agamid lizards; evolution; zvířata; Sex Determination Analysis; Snakes; procesy určující pohlaví; Female; syntenie